KEKUASAAN MAJELIS PERMUSYAWARATAN RAKYAT: PROBLEMATIK DAN PENATAAN - Efendi, A'an (Veritas et Justitia, 2023)
People's Consultative Assembly (MPR) is an autonomous institution between the House of Representatives (DPR) and the Regional Representatives Council (DPD) but its powers are limited because it is periodic and incidental. Using doctrinal legal research with a statute and comparative approach, this research concludes, first, the problematic power of MPR from its position as an autonomous state institution that is attached to the state secretariat and budget but limited in authority because the exercise of its power is periodic and incidental, such as the power to change the Constitution or other powers which MPR may not implement within five, ten, or fifteen years and beyond during the term of office of MPR members, and secondly, how to restructure the powers of MPR by changing the position of MPR from an autonomous state institution to a joint session of the DPR and DPD by revising Article 2 paragraph (1) of the 1945 Constitution which was originally "MPR consists of members of the DPR and members of DPD" to "MPR consists of the the DPR and DPD". It is found that the repositioning of MPR from an autonomous institution to a joint session may serve to balance its periodic and incidental powers.